Robotic Solution for the Automation of E-waste Recycling - Brazier, James Phillip; Prasetyo, Judhi (Journal of Applied Science and Advanced Engineering, 2023)
This paper focuses on the issue of e-waste and the use of a 6 Axis Robotic manipulator to build and test an industrial robotic system to detect components of commonly disposed of E-waste, then disassemble and segregate the main components for proper disposal and recycling using OpenCV image capture, TCP connections between OpenCV and ESPON, Arduino integration for Servo control and 3D Printed fixtures for disassembly.